Effect of Carbon Reinforcement on the Properties of Seashell Ceramic Composite - Mohamed Hatta, Mohamed Nasrul; YEH, JIA REN; Kamarul Azhar Kamaruddin, (Research Progress in Mechanical and Manufacturing Engineering, 2024)
Seashells are a type of natural ceramic that has qualities comparable to human bones and teeth. The main component of seashells is calcium carbonate (CaCO3), which accounts for more than 90% of their weight and contains very few chemical components. The chemical makeup is quite similar to that of limestone powder. To create optimum flow in ceramics material, a variety of methods can be used. Binder and reinforcement are two factors that can help improve the bulk material's characteristics. Thus, ceramic composite materials from seashell reinforced with graphite is produced and investigated. The seashell will be obtained in Seremban's Port Dickson and the shell will then be crushed into powder 150µm. The parameter of the graphite used are based on the weightage of reinforcement of 0 wt%, 0.1 wt%, 0.2 wt% and 0.3 wt%. Then, density and porosity tests are two physical tests that are used to test the specimen. The specimen was subjected to flexural strength and impact testing as part of the mechanical testing. Moreover, an optical microscope and a scanning electron microscope (SEM) are used to determine the morphology and fracture mechanism of the specimen. The result of this study shows that the addition of graphite increases the strength of the specimen